2005
DOI: 10.1093/hmg/ddi127
|View full text |Cite
|
Sign up to set email alerts
|

Activating mutations of the tyrosine kinase receptor FGFR3 are associated with benign skin tumors in mice and humans

Abstract: Specific germline activating point mutations in the gene encoding the tyrosine kinase receptor FGFR3 (fibroblast growth factor receptor 3) result in autosomal dominant human skeletal dysplasias. The identification in multiple myeloma and in two epithelial cancers-bladder and cervical carcinomas-of somatic FGFR3 mutations identical to the germinal activating mutations found in skeletal dysplasias, together with functional studies, have suggested an oncogenic role for this receptor. Although acanthosis nigricans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
165
2
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(195 citation statements)
references
References 36 publications
(26 reference statements)
14
165
2
10
Order By: Relevance
“…As FGFR3 is a gene involved in bladder carcinogenesis and the presence of FGFR3 mutations is also a common event in benign skin tumors, [30][31][32]35,37,41 this association between bladder, skin, and prostate cancer could suggest a common role for FGFR3 in their pathogenesis. However, the mutational analysis of the corresponding bladder tumors and normal prostate samples in some of the patients from our study revealed the wild-type status of the gene.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As FGFR3 is a gene involved in bladder carcinogenesis and the presence of FGFR3 mutations is also a common event in benign skin tumors, [30][31][32]35,37,41 this association between bladder, skin, and prostate cancer could suggest a common role for FGFR3 in their pathogenesis. However, the mutational analysis of the corresponding bladder tumors and normal prostate samples in some of the patients from our study revealed the wild-type status of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in this gene have been reported in bladder and cervix carcinoma, multiple myeloma, colon cancer and, more recently, in benign skin tumors. [25][26][27][28][29][30][31][32][33] The relatively high prevalence of FGFR3 mutations in benign skin tumors and in noninvasive bladder tumors suggests an association of FGFR3 mutation with low risk cancers. 35,41 Although it seems that anomalous FGF signaling is involved in prostate carcinogenesis, the functional role of FGFR3 and its alterations in prostate cancer are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGFR3 mutations have been identified in 39-85% of human seborrheic keratoses. 5,6 In patients with FGFR3 mutant seborrheic keratoses, normal skin showed a wild-type FGFR3 sequence confirming the somatic nature of these mutations. Albeit an important role of FGFR3 mutations in the pathogenesis of seborrheic keratoses is suggested by previous studies, details of the mechanisms causing these mutations in human epidermis and of the signaling pathways mediating the growth of acanthotic tumors in FGFR3 mutant skin are unknown.…”
mentioning
confidence: 83%
“…Recently, activating FGFR3 mutations in the epidermis were shown to be involved in the development of seborrheic keratoses. 5 Transgenic mice expressing the S249C FGFR3 mutation in the basal layer of the epidermis under the control of the keratin 5 promoter developed thickening of the skin and verrucous skin tumors with histological features similar to human seborrheic keratoses. FGFR3 mutations have been identified in 39-85% of human seborrheic keratoses.…”
mentioning
confidence: 99%